Antimicrobial bio-nanocomposites and their potential applications in food packaging - Sharma, Ruchi; Jafari, Seid Mahdi; Sharma, Somesh (Food control, 2020)
Bio-nanocomposites are bio-based polymers made up of two major components in which one acts as a matrix called biopolymer (continuous phase) and second called as reinforcement agent (dispersed phase) with dimensions in the range of 1–100 nm. These exhibit typical characteristics such as flexibility, biocompatibility, biodegradability, eco-friendliness, and cost-effectiveness which can be further enhanced by the reinforcement components. Bio-nanocomposites can be modified by fusion of nanofillers such as MMT (montmorillonite), AgO, TiO2, SiO2, ZnO and biodegradable polymers including polyhydroxylbutyrate (PHB), polybutylene succinate (PBS), polylactic acid (PLA) and poly-caprolactone (PCL), along with natural biopolymers such as starch and chitosan. Incorporation of antimicrobial agents into the food packaging materials inhibits the growth of microorganisms on food surfaces and thus increases their shelf life. The various experimentally designed antimicrobial nanocomposites are PLA/halloysite, PLA/Ag nanoparticles, hydroxyapatite/titania, layered silicate, and cellulose nanofibers which could inhibit the growth of different pathogens such as Listeria monocytogenes, Escherichia coli, and B. subtilis. These advantageous properties of antimicrobial bio-nanocomposites suggest their practical use in the food packaging industry.